Analisis Aktivitas Bongkar Muat Kapal Untuk Eliminasi Pemborosan di PT. Pelayaran Timur Asri Laut - Faisal Rizky Syahputra; Dzakiyah Widyaningrum; Hidayat Hidayat (Jurnal Serambi Engineering, 2022)
PT. Pelayaran Timur Asri Laut is the loading and unloading service company of various types of commodities. In the service process, operational performance is considered not optimal or there is waste which indirectly has an impact on the longer the berthing time of the ship, causing port congestion. The implementation of this study involves various activities such as identifying waste, analyzing the causes of waste occurring using the Lean Six Sigma method. The purpose is to analyze ship loading and unloading by identifying waste, analyzing the causes of waste  and the factors causing demurrage in PT. Sea East Voyage. The results showed that the factors causing the highest waste category demurrage occurred in the Internal Equipment Breakdown, then using a fishbone diagram and FMEA for the factors causing of the problem to get the highest RPN value. The 5 highest causes of the RPN value are the Operator not in accordance with the SOP, short lifetime, monitoring has not been measured in real terms, the quality of spare parts is not good and the procurement of spare parts is not coordinated.